APPLIED BACCALAUREATE PROGRAMS FOR THE ORENBURG REGION ELECTRICITY INDUSTRY - Vladimir M. Vakulyuk; Sergey V. Mitrofanov; Victor A. Morozov (Высшее образование в России)
The article is devoted to the problem of ensuring the quality of bachelor’s degree programs in electrical power engineering. The authors discuss the core principles and features of the organization of applied baccalaureate programs in the conditions of the FSES and FSES3+. The analysis of the current state of the energy industry in the Orenburg region is presented and the need for engineering personnel is substantiated.